German-US trade relations before the election: Implications of a Trump comeback - Andreas Baur; Lisandra Flach; Dorothee Hillrichs (EconPol Forum, 2024)
The US is Germany's largest trading partner, accounting for 11 percent of German exports and 7 percent of imports in 2023. Services comprise nearly 50 percent of German imports from the US and 30 percent of exports to the US, underscoring their significance in bilateral trade. Germany maintains a large trade surplus with the United States, equivalent to approximately 2.1 percent of Germany's GDP in 2023. One major driver of the surplus is a substantial increase in German goods exports to the US in recent years while German goods imports from the US have stagnated. In terms of value-added, around 7 percent of Germany's manufacturing value-added is exported to the US, compared to only 0.8 percent of US value-added exported to Germany, highlighting the importance of US market access for the German economy. A simulation exercise shows significant decreases in German exports to the US and China in response to potential new tariffs that Presidential candidate Donald Trump announced in his campaign. However, trade diversion in form of increasing trade between Germany and other countries partially offsets the negative direct effect of US tariffs, resulting in a 2 percent overall decrease in German exports. Germany and the EU should prioritize deepening its single market, especially in services, to remain an attractive US trade partner. Simultaneously, the EU should pursue new trade agreements to mitigate risks from potential US protectionist measures.
Keywords: 330